(untitled) (Research, Society and Development, 2021)
In Rio Grande do Sul State (RS), Brazil, the negative impacts of the pandemic were noticed in March of 2020, with various sectors suffering the impacts, such as industry, wholesale, and retail. Milk production has always been historically present and part of human development, especially in the Taquari Valley region, as it represents the basis of the economy of most small rural properties in the surrounding counties. Considering the difficulty observed by small-scale milk producers to adapt to the new daily procedures on the properties in the face of the COVID-19 pandemic, the present study aimed to assess changes in the routines of rural producers in view of the health situation, preventive care, and important factors in tackling the pandemic in Taquari Valley and Serra Gaúcha (RS). An exploratory study applied on 51 farms revealed that the vast majority have adopted safe practices, such as hand washing and using hand sanitizers and masks. The price of milk, the need to change milk management, and technical assistance during the COVID-19 pandemic are the most concerning factors for 96% of the respondents. Although the pandemic has pointed out several economic problems, the majority (88%) of the producers do not intend to abandon the dairy activity in this scenario that the world faces.